Meaning and Grammar in the light of Corpus Pattern Analysis. (21st December 2020) - Hanks, Patrick; Ma, Wulin
Abstract: This article presents an interview with Professor Patrick Hanks, a British lexicographer and corpus linguist, who proposes a new approach – a corpus-driven, phraseological approach – to lexicography. Hanks has developed a procedure called Corpus Pattern Analysis (CPA), which is the foundation of The Pattern Dictionary of English Verbs (in progress). The basic aim of CPA is to explore the relationship between word meaning and patterns of word use. Hanks maintains that the verb is 'the pivot of the clause'. Verb meanings – or, rather, the meanings of clauses – are mapped onto phraseological patterns, rather than just being listed for words in isolation. Associated with this is the Theory of Norms and Exploitations (TNE), which was discussed in his monograph published by MIT Press in 2013. In this interview, Professor Hanks outlines his vision of a phraseological dictionary of the future (an alternative to WordNet). He discusses meaning and grammar in the light of Corpus Pattern Analysis. Specifically, he explains the procedure of Corpus Pattern Analysis, and the objectives of the Pattern Dictionary of English Verbs (PDEV), including the light that such work can shed on the relationship between language and logic. He discusses the relationship between PDEV and English grammar, his evaluation of generative linguistics, and his views on Noam Chomsky. He also highlights the contributions made by linguists of the past to the understanding of the nature of meaning in language. He goes on to suggest that any new bilingual dictionary with Chinese as a source language should be based on careful analyses of actual language use, both in Chinese and in the various target languages.